EVALUATING READING SYLLABUS OF ISLAMIC UNIVERSITY THROUGH CURRICULUM IDEOLOGY - Fikrunnisa Sahlan; Gunawan Mansur; Ahmed Djoumoi (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2018)
Abstract:This study aimed to evaluate the syllabus from English Language Teaching (ELT) Department of an Islamic university in order to find out the integration of curriculum ideology. Reading II which one of the courses in ELT department of Universitas Islam Malang (Unisma) was used as the object to conduct this study. Interview, documents, evaluation checklist, and guideline to evaluate the integration of curriculum ideology were used as research instrument. The result showed that Reading II course syllabus from ELT department in undergraduate program of Unisma did not include all components of syllabus. Moreover, ELT Department of Unisma was already precise in order to curriculum development process. However, the syllabus as a feature to reflect the curriculum ideology did not clearly show the integration of the vision and the missions of ELT department which were based on Islamic characteristics, entrepreneurship, and ICT-based learning.Abstrak:Penelitian ini bertujuan untuk mengevaluasi silabus Program Studi Pendidikan Bahasa Inggris di sebuah universitas Islam untuk menemukan pengintegrasian ideologi kurikulum. Reading II yang merupakan salah satu mata kuliah dalam Program Studi Pendidikan Bahasa Inggris di Universitas Islam Malang (Unisma) digunakan sebagai sampel untuk melakukan penelitian ini. Wawancara, dokumen-dokumen, daftar evaluasi, dan panduan untuk mengevaluasi pengintegrasian ideologi kurikulum digunakan sebagai instrumen penelitian. Hasil penelitian menunjukkan bahwa silabus mata kuliah Reading II di Program Studi S1 Pendidikan Bahasa Inggris di Unisma belum memasukan seluruh komponen silabus. Selanjutnya, Program Studi Pendidikan Bahasa Inggris Unisma sudah tepat dalam proses pengembangan kurikulum. Tetapi, silabus sebagai sarana perwujudan ideologi kurikulum tidak menunjukkan secara jelas adanya pengintegrasian visi dan misi Program Studi Pendidikan Bahasa Inggris yang berdasar pada karakter Islam, kewiraswastaan, dan pembelajaran berbasis ICT.